Insuring your donation: An experiment - Renate Buijze; Christoph Engel; Sigrid Hemels (Max Planck Institute for Research on Collective Goods, 2015)
An increasing fraction of donations is channeled through donation intermediaries. These entities serve multiple purposes, one of which seems to be providing donors with greater certainty: that the donation reaches its intended goal, and that the donor may be sure to get a tax benefit. We interpret this function as insurance and test the option to insure donations in the lab. Our participants indeed have a positive willingness to pay for insurance against either risk. Yet the insurance option is only critical for their willingness to donate to a charity if the uncertainty affects the proper use of their donation.
Keywords: D64; H25; D03; H31; D12; G22; K34; L31; 330; insurance; charity; donation; donation intermediary